Enactive psychiatry - Haan, Sanneke de (Cambridge University Press, 2020)
The need for a model -- Currently available models in psychiatry -- Introduction to enactivism -- Body and mind -- and world -- The existential dimension and its role in psychiatry -- Enriched enactivism : existential sense-making, values, and socio-cultural worlds -- Enactive psychiatry : psychiatric disorders are disorders of sense-making -- An enactive approach to causes, diagnosis and treatment of psychiatric disorders.